KONSELING KELOMPOK TEKNIK REINFORCEMENT UNTUK MENINGKATKAN KEDISIPLINAN SISWA - Triana, Triana; Supriyatno, Arie (Universitas Muhammadiyah Magelang, 2014)
This research is aimed to examine the effectiveness of reinforcement by grouping counceling service to increase the student’s discipline. This research was done to the student’s of Al-Washliyah Islamic Junior High School Bandongan. The research design used in this research was an action research by giving grouping counceling service. It used three cycle, they are cycle 1, cycle 2 and cycle 3 that consist of four steps, planning, action, observation and reflection. Each cycle was done by three times action. The collective data methode were observation, interview and documentation. The subject of the research were 8 student’s, then they were analyzed using constant percentage with minimum target of 50 %. The result of this research showed that giving reinforcement by grouping counceling service is effective to increase the student’s discipline. It is proofed by the last average accomplishment the frequent change of the student’s discipline up to 69 %. The change of those numbers can be seen from the change of behaviour from less discipline become more discipline in before and after given the action. In conclusion giving reinforcement by grouping counceling service is effective to increase the student’s discipline of the 8th graders of MTs Al-Washliyah Bandongan Magelang.